Phase stability and tunable structural, hyperfine, and magnetic properties of Sol–Gel FeNi nanoparticles - Martínez, M.A.R.; Aragón, F.F.H.; Félix, L.L.; Mantilla, J.; Sousa, M.H.; Mathpal, M.C.; Felix, J.F.; Coaquira, J.A.H. (Elsevier, 2026)
In this study, Fe50Ni50 powder alloys were synthesized successfully using the sol–gel method, followed by systematic thermal treatments up to 1000 °C in a reducing atmosphere (Ar-H). Synchrotron X-ray diffraction patterns indicate that the data are well modeled by face-centered cubic (FCC) FeNi phase. The stability of this phase was studied, revealing that as the temperature is increased, the unit cell volume changes, suggesting an enhancement in the migration of iron atoms. This migration alters the stoichiometry of the FeNi alloy, potentially shifting it beyond its nominal 50/50 composition. High resolution TEM demonstrated the formation of the FeNi phase, which is in good agreement with the results obtained by XRD. Additionally, only a slight increase in crystalline particle size was observed. Magnetic characterization shows that thermal annealing strongly influences the magnetization. In particular, the sample annealed at 700 °C exhibits the highest magnetization and a Curie temperature 805 K, highlighting the role of thermal treatments in tuning the magnetic response. Zero-field cooling and field cooling measurements in the range 5–380 K further reveal irreversibilities above room temperature, attributed to the small particle size and strong interparticle interactions, which significantly affect the coercive field and overall magnetic behavior. These FeNi nanoparticles were characterized as magnetically soft materials. Mössbauer spectroscopy confirms the ferromagnetic behavior of the cubic FeNi phase as shown by XRD. Increasing the treatment temperature produces an increase in the hyperfine magnetic field, while the IS becomes more negative, which is primarily attributed to modifications in the s-electron density at the iron nuclei resulting from thermally induced electronic redistribution.
Keywords: Electrolyzers; https://purl.org/pe-repo/ocde/ford#2.04.01